The Intricate Role of p53 in Adipocyte Differentiation and Function - Yun Kyung Lee; Yu Seong Chung; Ji Hye Lee; Jin Mi Chun; Jun Hong Park (Cells, 2020)
For more than three decades, numerous studies have demonstrated the function of p53 in cell cycle, cellular senescence, autophagy, apoptosis, and metabolism. Among diverse functions, the essential role of p53 is to maintain cellular homeostatic response to stress by regulating proliferation and apoptosis. Recently, adipocytes have been studied with increasing intensity owing to the increased prevalence of metabolic diseases posing a serious public health concern and because metabolic dysfunction can directly induce tumorigenesis. The prevalence of metabolic diseases has steadily increased worldwide, and a growing interest in these diseases has led to the focus on the role of p53 in metabolism and adipocyte differentiation with or without metabolic stress. However, our collective understanding of the direct role of p53 in adipocyte differentiation and function remains insufficient. Therefore, this review focuses on the newly discovered roles of p53 in adipocyte differentiation and function.